Declining native fish, diminishing livelihood security: the predicament of Indian Himalayan communities. Issue 2 (3rd April 2021) - Gupta, Nishikant; Everard, Mark; Namchu, Chhaya Vani
ABSTRACT: Native fish species provide significant ecosystem services, including as food (provisioning services), as organisms with specific cultural and spiritual importance (cultural services), and contributions to supporting and regulatory services across the Indian Himalayan biodiversity hotspot. Fisheries in the Himalayan midhills and foothills, including in the Shivalik Hills and parts of the Terai (between the lower Himalayan foothills and the plains), provide livelihood security and cultural values for millions of people. Multiple anthropogenic stressors compounded by climate change have significantly depleted native fish populations over recent decades. Literature survey, focus group discussions and semi-structured interviews reveal that the decrease in native fish species undermines freshwater-dependent livelihood security in the region with 'knock-on' impacts on downstream ecosystem functions and services. Better understanding of the current distribution, habitat requirement and dispersal of native fish species important from a local perspective is essential to manage the growing threats to livelihoods in the Indian Himalayan region.